Making it happen: The pivotal role of knowledge sharing for information technology deployment success during joint venture change1. (May 2018) - Eaves1, Sally; Kumar, Vikas; White, Gareth R. T.; Loonam, John
Abstract : Tacit and explicit knowledge sharing must be continually cultivated to enable information technology implementation success. Effective information technology deployment necessitates a holistic focus beyond technical and legacy factors to include social, organizational, political, and interpersonal dimensions. Attention to cultural integration is a critical component of managing joint venture change and building employee engagement, perception of legitimacy and knowledge sharing norms. Individual employees occupy a key role in determining intended strategic impacts by committing to and enacting change efforts, particularly though making discretionary decisions to share their knowledge or alternatively to hoard, hide or disengage from sharing; an outcome which may be influenced by perceptions on knowledge ownership and value.